1992
DOI: 10.1002/cber.19921250530
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Conjugate Addition of Dialkylzinc Compounds to Chalcones

Abstract: Conjugate addition of diethylzinc to enones is catalyzed by a complex derived from Ni(acac)2 and C2-symmetric 2,2'-bipyridine 3 or chiral pyridines 5-12. The products are obtained with optical purities up to 89% ee. A strong positive nonlinear relationship between the enantiomeric excess of the ligand and the ee of the product has been observed. The factors which govern catalyst activity and enantioselectivity have been investigated.Carbon -carbon bond formation by conjugate addition of organometallic reagents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
2
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(36 citation statements)
references
References 72 publications
0
32
2
2
Order By: Relevance
“…Reetz noticed a (+)-NLE in the rhodium-catalyzed hydrogenation of olefin 161 in the presence of binol-derived monodentate phosphite 162 a [Eq. (50)]. [144] The theoretical curve, based on an ML 2 model with K = 4 and g = 0, was found to fit well with the experimental curve, and the stochastic formation of catalytically active homochiral and catalytically inactive heterochiral complexes was proposed.…”
Section: Reviewsmentioning
confidence: 96%
See 1 more Smart Citation
“…Reetz noticed a (+)-NLE in the rhodium-catalyzed hydrogenation of olefin 161 in the presence of binol-derived monodentate phosphite 162 a [Eq. (50)]. [144] The theoretical curve, based on an ML 2 model with K = 4 and g = 0, was found to fit well with the experimental curve, and the stochastic formation of catalytically active homochiral and catalytically inactive heterochiral complexes was proposed.…”
Section: Reviewsmentioning
confidence: 96%
“…Bolm et al [50] and Feringa and co-workers [51] reported (+)-NLEs for nickel-catalyzed 1,4-additions to enones. The authors proposed the intervention of [NiL 2 ] species in the catalytic cycle.…”
Section: Conjugate Additions To Enonesmentioning
confidence: 97%
“…7,8 Bolm et al developed a series of substituted pyridyl alcohols in asymmetric diethylzinc addition to aldehydes and conjugate addition reactions of diethylzinc to chalcones. [9][10][11] They also reported the use of C2-symmetric chiral bipy ligands in enantioselective conjugate addition reactions such as diethylzinc addition to aldehydes, and enantioselective addition of alcohols and amines to meso-epoxides. [12][13][14] Lee described Monopyridyl bisimine ligands in Ru-catalyzed cyclopropanation of styrene.…”
Section: Introductionmentioning
confidence: 96%
“…[4] Further examples include palladium-catalysed allylic substitution reactions, [5] nickel-catalysed additions of organozinc compounds to enones [6] and asymmetric alkynylations of aldehydes. [7] Typically, enantiopure (hydroxymethyl)pyridine derivatives are prepared through asymmetric reductions of the corresponding ketones, diastereoselective additions of lithiated pyridine derivatives to chiral ketones or through resolution of racemic compounds.…”
Section: Introductionmentioning
confidence: 99%